Comments on the neotype of Rana margaritifera Laurenti, 1768 (Anura, Bufonidae) - Lavilla, Esteban O.; Langone, José A.; Caramaschi, Ulisses; Pombal, José P. Jr.; Sá, Rafael O. De (Zootaxa, 2017)
After more than two and half centuries regarding the identity of Rana margaritifera Laurenti, 1768, Lavilla et al. (2013) designated a neotype for the species. The authors did an extensive search to locate the type material of Laurenti (1768) and failed in finding the specimen in question. Consequently, they selected an adult female collected in the Municipality of Humaitá, State of Amazonas, Brazil, on 12 April 1985 and deposited in the Museu Nacional, Rio de Janeiro, Brazil, MNRJ 71538. This action, was carried out to solve a specific taxonomic problem in Neotropical amphibian systematics, i.e., the type specimen considered lost and the type locality uncertain. However, this action proved to be erroneous, since the type specimen is not lost.